The precarious situation of agricultural wage laborers in Myanmar - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2022)
To understand the effects of COVID-19, the political crisis, and other shocks on Myanmar’s agricultural wage laborers (those workers relying on casual labor in agriculture), we rely on data from three rounds of the Myanmar Household Welfare Survey and two rounds of the Myanmar Agricultural Performance Survey, fielded in 2021 and 2022.